Semiotic Introduction of Peircean Theory in Indonesian Cultural Tradition Celebrating Victory and Purification in The Month of Syawwal "Halal Bi Halal” - Zahra, Shafirany Arafah Zahra; Rusmana, Dadan; Sakinah, R. Myrna Nur (Suara Bahasa, 2024)
Indonesian Muslim society observes a distinctive annual tradition known as "Halal bi halal," which is closely linked to the celebration of Eid al-Fitr following the fasting month of Ramadan in the month of Shawwal. This communal activity is found to be beneficial for participants. The primary aim of this research is to explore the semiotic perspective, unveiling the meanings conveyed through signs and symbols embedded in this tradition. The findings of the data analysis are presented descriptively, using a qualitative approach. The outcomes reveal two key aspects: (1) the use of the respectful speech level, and politeness when addressing older individuals, and (2) the inherent meanings within the tradition, specifically centered around the notions of respect and the promotion of harmony in life. In conclusion, the "Halal bi halal" tradition is intentionally crafted to safeguard the most valuable cultural values in society through the strategic use of signs and symbols.